Analisis Penerapan Biaya Standar terhadap Pengendalian Biaya Produksi pada PG Poerwodadie - Izzatul Ashif; Qimyatus sa’adah; Halleina Rejeki Putri Hartono (Universitas Merdeka Madiun, 2020)
Abstract— Competition in the business world requires companies to be able to manage their production cost effectively and efficiently. One of the method that can be use to controlling production cost is a standard cost. This research aims to analyze the implementation of standard cost on controlling of production cost at PG Poerwodadie. The data collection technique are used by interview, documentation, and data triangulation. Data analysis in this research is done by setting the standard cost and analyzing using the two-way model variance. The results of the research indicate that between the standard cost and actual cost incurred by PG Poerwodadie there is a favorable variance of Rp 2,667,683,61, which consist of raw material cost variance amounting to Rp 2.173.301.277 (favorable), direct labor cost variance amounting to Rp 539.403.640 (unfavourable), and factory overhead cost variance amounting to Rp 1.033.785.975 (favorable). Keywords—: standard cost; production cost; variance analysis.